Cleaning process for alloy parts for semiconductors

CN122913143APending Publication Date: 2026-10-16SUZHOU LINGHE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611101697.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

人工擦拭主要作用于外露表面,对螺纹孔、盲孔、凹槽、流道和配合面内部的嵌顿颗粒清除能力不足,且容易因擦拭不均造成清洁效果波动

Benefits of technology

[0027] (1) This invention uses deionized water, sodium carbonate, sodium bicarbonate, and sodium citrate to form a weakly alkaline base solution, and combines it with sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, and isopropanol to improve the wetting and penetration ability of oil stains, cutting fluid, and fine particles on the surface of alloy parts for semiconductors. The sodium phytate-glucan silane alloy protection compound can form a complex adsorption and silane composite protection effect on the alloy surface, reducing the risk of graying, corrosion, and surface roughening of the alloy matrix during the weakly alkaline cleaning process, so that the cleaning process has both decontamination ability and matrix protection effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of cleaning process of alloy parts for semiconductor in the technical field of semiconductor precision parts surface cleaning;Including weak base composite cleaning solution preparation, parts pre-depulping and grading cleaning steps.Weak base composite cleaning solution contains deionized water, sodium carbonate, sodium bicarbonate, sodium citrate, sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, isopropyl alcohol, phytic acid sodium silane compound and carboxy betaine polyether silicon stripping compound.After surface pretreatment, drying compressed air back flushing and high pressure deionized water after washing, weak base ultrasonic rough cleaning, deionized water rinsing, high pressure after washing, isopropyl alcohol aqueous solution ultrasonic cleaning, spray flushing, immersion rinsing, overflow rinsing, drying and post-processing are carried out in turn.The application can improve the wetting and stripping ability of cleaning solution to silicon powder in machining texture and micropore, reduce the secondary adhesion of silicon powder, and reduce the corrosion risk of aluminum-based alloy parts in weak base cleaning process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface cleaning technology for semiconductor precision components, and specifically relates to a cleaning process for alloy components used in semiconductors. Background Technology

[0002] Semiconductor equipment and its precision components have high requirements for surface cleanliness, particle residue, corrosion status, and subsequent stability. During machining, drilling, grooving, milling, polishing, and pre-assembly treatment, alloy components are prone to surface residues of cutting fluid, oil, fine metal shavings, silicon powder, oxide debris, and small particles embedded in machining textures and micropores. For high-silicon aluminum-based alloys, aluminum-silicon composite alloys, and other semiconductor alloy components used for heat dissipation, support, positioning, and fluid channels, if surface residues cannot be effectively removed, problems such as continuous powder shedding, cavity contamination, flow channel blockage, scratching of sealing surfaces, or affecting assembly accuracy can easily occur during subsequent use, thereby reducing the reliability and stability of semiconductor equipment during operation. Therefore, establishing a cleaning process that balances decontamination, powder removal, alloy protection, prevention of secondary adhesion, and low-damage operation is of great significance.

[0003] Current methods for cleaning semiconductor alloy components primarily employ manual wiping, ordinary water washing, single-solvent immersion, conventional alkaline cleaning, or ordinary ultrasonic cleaning. Manual wiping mainly targets exposed surfaces and is insufficient for removing embedded particles from threaded holes, blind holes, grooves, flow channels, and mating surfaces. Furthermore, uneven wiping can lead to fluctuating cleaning results. While ordinary water washing and single-solvent immersion can remove some loose powder and oil, they lack sufficient removal ability for silicon powder and fine particles deep within the machining texture. Strong alkaline cleaning can improve degreasing ability but may accelerate corrosion of aluminum-based alloy surfaces, leading to graying, roughening, or decreased dimensional accuracy. Ordinary ultrasonic cleaning, without appropriate dispersion, anti-redeposition, and alloy protection systems, can easily cause detached particles to re-adhere to the component surface in the cleaning solution, leaving the cleaned components with the potential for further powder shedding.

[0004] Furthermore, existing processes typically lack pre-treatment to remove loose particles after machining. When components directly enter the cleaning solution, large amounts of silicon powder and metal shavings quickly contaminate the cleaning tank, increasing the turbidity and particle load of the cleaning solution, leading to secondary pollution. While some processes incorporate high-pressure water rinsing or ultrasonic rinsing, the lack of coordinated design between these steps makes it difficult to simultaneously achieve microporous particle removal, oil removal, aluminum substrate protection, particle dispersion and suspension, and final watermark control. Especially for complex structures such as threaded holes, blind holes, grooves, flow channels, mating surfaces, and sealing surfaces of semiconductor alloy components, relying on a single cleaning method is insufficient to achieve stable cleanliness. Therefore, there is an urgent need for a cleaning process that combines a weakly alkaline composite cleaning solution, pretreatment reverse purging, high-pressure deionized water replenishment, ultrasonic graded cleaning, isopropanol aqueous solution replacement, multi-stage deionized water rinsing, drying, and post-treatment to address the problems of incomplete cleaning, secondary silicon powder adhesion, susceptibility to aluminum substrate corrosion, and difficulty in removing residual particles from complex structures in existing technologies. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a cleaning process for alloy components for semiconductors.

[0006] In a first aspect, the present invention provides a cleaning process for alloy components for semiconductors, comprising the following steps:

[0007] S1. By weight, mix 100.0-150.0 parts deionized water, 1.0-2.4 parts sodium carbonate, 0.4-1.2 parts sodium bicarbonate and 0.10-0.45 parts sodium citrate to obtain a weakly alkaline base solution; add 0.05-0.25 parts sodium dodecyl sulfate, 0.05-0.30 parts fatty alcohol polyoxyethylene ether, 2.0-6.0 parts isopropanol, 0.25-0.80 parts sodium phytate silane alloying compound and 0.35-1.20 parts carboxybetaine polyether desiliconizing compound to the weakly alkaline base solution, continue mixing, adjust the pH, filter, and obtain a weakly alkaline composite cleaning solution;

[0008] S2. Pre-treat the surface of the semiconductor alloy parts to obtain pre-polished parts; blow dry compressed air in the reverse direction along the processing texture of the pre-polished parts to obtain blown parts; use high-pressure deionized water to clean the threaded holes, blind holes, grooves, flow channels, mating surfaces and sealing surfaces of the blown parts to obtain pre-de-powdered parts.

[0009] S3. The pre-de-powdered parts are ultrasonically coarsely cleaned with 80.0-150.0 parts of weak alkaline composite cleaning solution to obtain coarsely cleaned parts; the coarsely cleaned parts are ultrasonically rinsed and ultrasonically finely rinsed with deionized water to obtain rinsed parts; the rinsed parts are scanned and cleaned line by line with high-pressure deionized water to obtain cleaned parts; the cleaned parts are ultrasonically cleaned with isopropanol aqueous solution, and then sprayed, immersed, and overflowed with deionized water in sequence, dried and post-treated.

[0010] In this invention, the cleaning process mechanism for semiconductor alloy components is a continuous synergistic process of pre-powder removal, weak alkali wetting, ultrasonic stripping, stepwise migration, and low-residue drying. In the weak alkali composite cleaning solution, deionized water acts as both a solvent and a particle migration medium. Sodium carbonate and sodium bicarbonate form a mild buffer environment, which is beneficial for loosening cutting fluid and oil stains while avoiding significant corrosion of the alloy substrate by strong alkali. Sodium citrate complexes the free metal ions in the cleaning solution, reducing the tendency of particles to stick back due to ion bridging. Sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, and isopropanol work together to reduce the surface tension of the cleaning solution, making it easier for the cleaning solution to penetrate the machining texture, threaded holes, blind holes, grooves, flow channels, mating surfaces, and sealing surfaces. The sodium phytate-glucan silane alloy protection compound preferentially acts on the alloy surface and oxide film defects in the weak alkali environment. Through complexation adsorption and the silane composite structure, it reduces the risk of local corrosion and protects the alloy substrate from the effects of prolonged immersion in the cleaning solution. The carboxybetaine polyether silicon stripping compound fully wets, loosens, disperses, and keeps silicon powder and fine particles in suspension. Surface pretreatment of components removes burrs, rough spots, and loose contaminants. Dry compressed air blows against the machining texture to detach loosely embedded powder particles. High-pressure deionized water rinse further flushes out residual particles from threaded holes, blind holes, and dead corners of flow channels. After ultrasonic rough cleaning, the micro-jets and localized impacts generated by ultrasonic cavitation loosen and detach embedded particles that have been wetted by a weak alkaline composite cleaning solution. Subsequently, ultrasonic rinsing with deionized water and ultrasonic fine rinsing remove detached particles, residual cleaning solution, and soluble impurities. Line-by-line scanning cleansing covers dead corners of complex structures. Isopropanol aqueous solution ultrasonic cleaning removes residual oil contaminants. Spray rinsing, immersion rinsing, and overflow rinsing continuously reduce particle load and cleaning agent residue. Drying and post-treatment reduce watermarks, floating powder, and surface residual liquid, resulting in semiconductor alloy components with low particle residue and good surface cleanliness stability after cleaning.

[0011] According to a preferred embodiment of the present invention, in step S1, the fatty alcohol polyoxyethylene ether is fatty alcohol polyoxyethylene ether AEO-9; and the pH is adjusted to 8.2-9.2.

[0012] According to a preferred embodiment of the present invention, in step S2, the pressure of the drying compressed air is 0.4-0.6 MPa, the reverse purging time is 5-8 min, and the rewashing time is 10-30 s.

[0013] According to a preferred embodiment of the present invention, in step S3, the temperature of the ultrasonic coarse cleaning is 40-60°C, the time of the ultrasonic coarse cleaning is 10-15 min; the time of the ultrasonic rinsing is 5-8 min; the time of the ultrasonic fine rinsing is 3-5 min; and the time of the line-by-line scanning replenishment cleaning is 10-30 s.

[0014] According to a preferred embodiment of the present invention, the preparation method of the phytate-glucosyl silane alloy compound includes:

[0015] A1. By weight, mix 65.0-85.0 parts deionized water, 8.0-14.0 parts sodium gluconate, 0.5-2.0 parts sodium citrate, and 1.0-4.0 parts polyethylene glycol 400, and stir at 35-45℃. Add 6.0-12.0 parts phytic acid aqueous solution, adjust the pH to 6.8-7.6 with ammonia water, and continue stirring to obtain a phytic acid-sodium gluconate pre-complexed solution; add 8.0-1... 4.0 parts anhydrous ethanol, 1.5-3.5 parts 3-aminopropyltriethoxysilane, 2.0-6.0 parts deionized water and 0.10-0.40 parts glacial acetic acid are mixed and hydrolyzed at 20-30℃ to obtain a silane pre-hydrolyzed solution; the silane pre-hydrolyzed solution is added to a sodium phytate pre-complexing solution, the pH is adjusted to 7.0-7.4 with ammonia water, and the mixture is stirred at 40-50℃ to obtain a sodium phytate silane composite solution;

[0016] A2. The phytate-glucosyl silane composite solution is aged at 40-55℃, cooled to 25-35℃, 0.05-0.15 parts of 1,2-benzisothiazolin-3-one are added, stirred, allowed to stand to defoam, and filtered.

[0017] In this invention, the formation mechanism of the sodium phytate-glucose silane complex mainly includes aqueous dissolution and dispersion, acid-base controlled association, silane hydrolysis, and aging and complexation processes. Deionized water serves as the continuous phase medium, ensuring uniform dispersion of sodium glucate, sodium citrate, and polyethylene glycol 400. The carboxylate and polyhydroxy structures in sodium glucate can form stable associations with the phosphate groups in the phytic acid aqueous solution through multiple hydrogen bonds and dipole interactions. The sodium ions present in the system act as counterions, providing local charge shielding and electrostatic stabilization for the multiple anionic groups of phytic acid, reducing electrostatic repulsion between anions, and facilitating the formation of stable hydrogen bond association structures between glucate and phytic acid phosphate. Sodium citrate improves the system's complexation stability against free metal ions and trace impurities, while polyethylene glycol 400 improves the spreadability and dispersion uniformity of the aqueous phase. After the addition of the phytic acid aqueous solution, ammonia adjusts the pH of the system, mitigating excessive acidity and preventing rapid coagulation of the silane components upon their introduction due to excessively high local acidity, thus forming a relatively stable sodium phytate-glucose pre-complexed solution. When anhydrous ethanol, 3-aminopropyltriethoxysilane, deionized water, and glacial acetic acid are mixed, the ethoxy group in 3-aminopropyltriethoxysilane undergoes gradual hydrolysis under the action of water and glacial acetic acid, generating a silane pre-hydrolyzed solution containing a silanol structure. After adding a sodium phytate pre-complexing solution to the silane pre-hydrolyzed solution, the silanol structure undergoes hydrogen bonding association, electrostatic adsorption, and partial siloxane condensation with the phosphate groups, carboxylates, and hydroxyl groups in the phytic acid aqueous solution, sodium gluconate, and sodium citrate. Ammonia water is used to adjust the system to a suitable weakly alkaline state, allowing the silanol to participate in the complexation without excessive self-condensation. After aging, a composite protective component is formed, consisting of the sodium phytate associated structure and the silane hydrolysis condensation structure. After cooling, 1,2-benzisothiazolin-3-one is added to maintain the stability of the aqueous system during storage. Static defoaming and filtration remove bubbles and a small amount of coarse agglomerates, giving the resulting sodium phytate silane alloying compound protective properties, corrosion inhibition, interfacial adhesion, and wetting regulation.

[0018] According to a preferred embodiment of the present invention, in step A1, the stirring and hydrolysis time at 20-30°C is 30-60 min; and the stirring time at 40-55°C is 1.0-2.5 h.

[0019] According to a preferred embodiment of the present invention, in step A2, the curing time at 40-55°C is 1.0-2.0 h, and the standing defoaming time is 1-3 h.

[0020] According to a preferred embodiment of the present invention, the method for preparing the carboxybetaine polyether desiliconized compound includes:

[0021] B1. By weight, mix 55.0-75.0 parts deionized water, 3.0-8.0 parts polyethylene glycol 400, 2.0-5.0 parts sodium citrate and 0.3-1.2 parts tetrasodium hydroxyethylidene diphosphonate, and stir at 35-45℃ to obtain a polyether dispersion base solution; add 8.0-15.0 parts cocamidopropyl betaine aqueous solution, 3.0-7.0 parts fatty alcohol polyoxyethylene ether and 4.0-8.0 parts isopropanol to the polyether dispersion base solution, and stir to obtain a betaine polyether compound solution;

[0022] B2. Add 2.0-5.0 parts of low molecular weight sodium polyacrylate aqueous solution to the betaine polyether compound solution, adjust the pH to 7.8-8.6, mature at 40-50℃, cool to 25-35℃, add 0.03-0.12 parts of polyether modified polydimethylsiloxane defoamer, stir, let stand to defoam, and filter.

[0023] In this invention, the formation mechanism of the carboxybetaine polyether desiliconizing compound mainly includes aqueous phase dispersion, complexation stabilization, surface-active compounding, particle suspension, and foam control processes. Deionized water provides a continuous dispersion medium. After polyethylene glycol 400 enters the aqueous phase, it improves the wetting and spreading ability of the system, making it easier for subsequent surface-active components to form a homogeneous compound system. Sodium citrate and tetrasodium hydroxyethylidene diphosphonate play a role in metal ion complexation and dispersion stabilization in the aqueous phase, which can reduce the bridging adsorption of metal ions between silicon powder, oxide debris, and alloy surfaces, thereby reducing the tendency for secondary particle adhesion. After the addition of cocamidopropyl betaine aqueous solution, its amphoteric surface-active structure can adsorb onto the interface between silicon particles and alloys in a weakly alkaline environment, weakening the adhesion between silicon powder and the processing texture. Fatty alcohol polyoxyethylene ether, as a nonionic wetting component, can synergistically reduce interfacial tension and improve the wetting ability of oil, cutting fluid, and particles within micropores. Isopropanol improves the permeability of the cleaning fluid to fine pores, blind holes, grooves, and flow channels, making it easier for the surface-active components to reach the particle embedding sites. When low molecular weight sodium polyacrylate aqueous solution is added to the betaine polyether compound solution, its carboxylate segments can adsorb onto the surface of the wetted and peeled silicon powder and fine particles, forming charge repulsion and steric hindrance, keeping the particles in a suspended and dispersed state and reducing redeposition. Polyether-modified polydimethylsiloxane defoamer disrupts stable foam films through hydrophobic siloxane segments and hydrophilic polyether segments, reducing foam barrier during stirring and ultrasonic cleaning. After maturation, cooling, defoaming, and filtration, the carboxybetaine polyether desiliconizing compound forms a stable wetting, exfoliation, and anti-redeposition composite system. Its desiliconizing effect is mainly manifested in interface wetting, ultrasonic cavitation synergistic exfoliation, and particle dispersion and suspension.

[0024] According to a preferred embodiment of the present invention, in step B1, the stirring time at 35-45°C is 20-40 min.

[0025] According to a preferred embodiment of the present invention, in step B2, the curing time at 40-50°C is 1-2 hours; the standing defoaming time is 1-3 hours.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) This invention uses deionized water, sodium carbonate, sodium bicarbonate, and sodium citrate to form a weakly alkaline base solution, and combines it with sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, and isopropanol to improve the wetting and penetration ability of oil stains, cutting fluid, and fine particles on the surface of alloy parts for semiconductors. The sodium phytate-glucan silane alloy protection compound can form a complex adsorption and silane composite protection effect on the alloy surface, reducing the risk of graying, corrosion, and surface roughening of the alloy matrix during the weakly alkaline cleaning process, so that the cleaning process has both decontamination ability and matrix protection effect.

[0028] (2) The present invention uses carboxybetaine polyether desiliconizing compound to enhance the wetting, peeling, dispersion and anti-re-adhesion effects of silicon powder and fine particles. The aqueous solution of cocamidopropyl betaine, fatty alcohol polyoxyethylene ether, aqueous solution of low molecular weight sodium polyacrylate, sodium citrate and tetrasodium hydroxyethylidene diphosphonate work together to weaken the adhesion between silicon powder and the processing texture, blind hole, groove and inner wall of flow channel, so that the detached particles remain in a suspended and dispersed state, reduce the re-adhesion of particles in the cleaning solution and secondary pollution, and improve the thoroughness of cleaning complex structural areas.

[0029] (3) The present invention combines surface pretreatment, reverse blowing with dry compressed air, high-pressure deionized water cleaning, ultrasonic rough cleaning with weak alkaline composite cleaning solution, ultrasonic rinsing with deionized water, ultrasonic fine rinsing with deionized water, high-pressure deionized water line-by-line scanning cleaning, ultrasonic cleaning with isopropanol aqueous solution, spray rinsing, immersion rinsing, overflow rinsing, drying and post-treatment in a continuous manner. This can remove loose floating powder first, then peel off embedded particles, and remove residual contaminants step by step, thereby reducing the risk of subsequent powder shedding and improving the surface cleanliness and service stability of alloy parts for semiconductors. Detailed Implementation

[0030] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0031] Example 1

[0032] This embodiment provides a cleaning process for alloy components used in semiconductors, including the following steps:

[0033] S1. Add 125.0g of deionized water to the cleaning solution preparation container, then add 1.7g of sodium carbonate, 0.8g of sodium bicarbonate and 0.275g of sodium citrate in sequence, and stir for 30min until completely dissolved to obtain a weakly alkaline base solution; add 0.15g of sodium dodecyl sulfate, 0.175g of fatty alcohol polyoxyethylene ether, 4.0g of isopropanol, 0.525g of phytate-glucopyranosilane alloy compound and 0.775g of carboxybetaine polyether desiliconizing compound in sequence to the weakly alkaline base solution, and continue mixing for 35min. Adjust the pH to 8.7 with citric acid solution or sodium carbonate solution, filter, and obtain a weakly alkaline composite cleaning solution;

[0034] S2. Take one semiconductor alloy component after machining (the semiconductor alloy component is made of T6-6061 aluminum alloy, and the dimensions of the semiconductor alloy component are: 100mm × width 100mm × thickness 20mm). Pre-treat the surface, thread hole edge, blind hole edge, groove edge, flow channel edge, mating surface and sealing surface of the semiconductor alloy component to remove surface burrs, rough spots and loose particles to obtain a pre-polished component. Blow dry compressed air at a pressure of 0.5MPa along the machining texture of the pre-polished component in the opposite direction for 6.5min to remove loose silicon powder and particles in the machining texture to obtain a blown component. Use 100.0g of high-pressure deionized water to clean the thread hole, blind hole, groove, flow channel, mating surface and sealing surface of the blown component for 20s to obtain a pre-de-powdered component.

[0035] S3. Place the pre-de-powdered parts in a cleaning container and perform ultrasonic rough cleaning for 12.5 minutes at 50°C using 115.0g of weak alkaline composite cleaning solution, ensuring the weak alkaline composite cleaning solution fully contacts the surface, threaded holes, blind holes, grooves, flow channels, mating surfaces, and sealing surfaces of the pre-de-powdered parts, resulting in rough-cleaned parts. Then, ultrasonically rinse the rough-cleaned parts with 100.0g of deionized water for 6.5 minutes, followed by ultrasonic fine rinsing with 100.0g of deionized water for 4 minutes, resulting in rinsed parts. Finally, perform a line-by-line scan cleanse of the rinsed parts with 100.0g of high-pressure deionized water for 20 seconds, resulting in replenished parts. Mix 80.0g of isopropanol and 20.0g of deionized water... The isopropanol aqueous solution was obtained. The repaired parts were ultrasonically cleaned with the isopropanol aqueous solution for 4.5 min, followed by spray rinsing with 100.0 g of deionized water for 2 min, immersion rinsing with 100.0 g of deionized water for 4 min, and overflow rinsing with 100.0 g of deionized water for 5.5 min. After rinsing, the residual liquid in the surface, threaded holes, blind holes, grooves and flow channels of the repaired parts was blown off with 0.35 MPa dry compressed air. Then, the parts were dried with hot air at 110℃ for 12.5 min. After drying, the mating surfaces, sealing surfaces, threaded holes and groove edges were post-treated to remove residual floating powder, and the cleaned semiconductor alloy parts were obtained.

[0036] Preparation steps of phytate-glucosyl silane alloy compound:

[0037] A1. Add 75.0g of deionized water to a reaction vessel and start stirring. Add 11.0g of sodium gluconate, 1.25g of sodium citrate, and 2.5g of polyethylene glycol 400 sequentially. Stir at 40℃ for 25 minutes to completely disperse and dissolve the sodium gluconate, sodium citrate, and polyethylene glycol 400, obtaining a homogeneous aqueous mixture. Add 9.0g of a 50% (w / w) phytic acid aqueous solution to the homogeneous aqueous mixture. Adjust the pH to 7.2 by adding ammonia dropwise. Continue stirring for 30 minutes to obtain phytic acid pre-sodium gluconate. Complexing solution; In a separate reaction vessel, add 11.0 g anhydrous ethanol, 2.5 g 3-aminopropyltriethoxysilane, 4.0 g deionized water and 0.25 g glacial acetic acid, and stir and hydrolyze at 25 °C for 45 min to obtain silane pre-hydrolyzed solution; Slowly add the silane pre-hydrolyzed solution to the sodium phytate pre-complexing solution while stirring to ensure uniform dispersion of the silane pre-hydrolyzed solution in the sodium phytate pre-complexing solution, and then add ammonia water dropwise to adjust the pH to 7.2. Stir at 45 °C for 1.75 h to obtain sodium phytate silane composite solution;

[0038] A2. The phytate-glucosyl silane composite solution was aged at 47.5℃ for 1.5h. After aging, the temperature was lowered to 30℃, and 0.10g of 1,2-benzisothiazolin-3-one was added. The mixture was stirred for 20min to ensure that 1,2-benzisothiazolin-3-one was uniformly dispersed in the system. The mixture was then allowed to stand for 2h to defoam. After defoaming, the mixture was filtered to remove undispersed aggregates and residual bubbles, thus obtaining the phytate-glucosyl silane alloy compound.

[0039] Preparation steps of carboxybetaine polyether desiliconized compound:

[0040] B1. Add 65.0g of deionized water to the reaction vessel and start stirring. Then add 5.5g of polyethylene glycol 400, 3.5g of sodium citrate, and 0.75g of tetrasodium hydroxyethylidene diphosphonate in sequence. Stir at 40℃ for 30min to fully dissolve and disperse the polyethylene glycol 400, sodium citrate, and tetrasodium hydroxyethylidene diphosphonate to obtain a polyether dispersion base solution. Add 11.5g of 30% cocamidopropyl betaine aqueous solution, 5.0g of fatty alcohol polyoxyethylene ether, and 6.0g of isopropanol in sequence to the polyether dispersion base solution. Continue stirring for 40min to ensure that all components are completely mixed and homogeneous to obtain a betaine polyether compound solution.

[0041] B2. Add 3.5g of a 40% (w / w) aqueous solution of low molecular weight sodium polyacrylate (weight average molecular weight of low molecular weight sodium polyacrylate is 2000-5000) to the betaine polyether compound solution, and continue stirring for 30min to uniformly disperse the low molecular weight sodium polyacrylate aqueous solution in the betaine polyether compound solution. Adjust the pH to 8.2 by adding citric acid solution or sodium carbonate solution dropwise, and mature at 45℃ for 1.5h. After maturity, cool down to 30℃, add 0.075g of polyether modified polydimethylsiloxane defoamer, continue stirring for 20min, let stand for 2h to defoam, filter after defoaming to obtain carboxylated betaine polyether desiliconized compound.

[0042] Example 2

[0043] The difference between this embodiment and Embodiment 1 is that this embodiment provides a cleaning process for semiconductor alloy components, including the following steps:

[0044] S1. Add 100.0g deionized water, 1.0g sodium carbonate, 0.4g sodium bicarbonate and 0.10g sodium citrate to the cleaning solution preparation container and stir until completely dissolved to obtain a weakly alkaline base solution; add 0.05g sodium dodecyl sulfate, 0.05g fatty alcohol polyoxyethylene ether, 2.0g isopropanol, 0.25g sodium phytate silane alloy compound and 0.35g carboxybetaine polyether desiliconizing compound to the weakly alkaline base solution, continue mixing for 30min, adjust the pH to 8.2, filter, and obtain a weakly alkaline composite cleaning solution;

[0045] S2. The surface of the machined semiconductor alloy parts is pretreated to remove burrs, rough spots and loose particles to obtain pre-polished parts; dry compressed air at a pressure of 0.4 MPa is used to blow along the machining texture of the pre-polished parts in the opposite direction for 5 minutes to obtain blown parts; the threaded holes, blind holes, grooves, flow channels, mating surfaces and sealing surfaces of the blown parts are cleaned with 80.0 g of high-pressure deionized water for 10 seconds to obtain pre-de-powdered parts;

[0046] S3. The pre-de-powdered parts are ultrasonically coarsely cleaned for 10 minutes at 40°C with 80.0g of weak alkaline composite cleaning solution to obtain coarsely cleaned parts; the coarsely cleaned parts are ultrasonically rinsed with 80.0g of deionized water for 5 minutes, and then ultrasonically finely rinsed with 80.0g of deionized water for 3 minutes to obtain rinsed parts; the rinsed parts are then scanned line by line with 80.0g of high-pressure deionized water for 10 seconds to obtain replenished parts; 70.0g of isopropanol and 30.0g of deionized water are mixed to obtain an isopropanol aqueous solution, and the replenished parts are ultrasonically cleaned with the isopropanol aqueous solution, and then sequentially sprayed with 80.0g of deionized water, immersed in 80.0g of deionized water, and overflowed with 80.0g of deionized water, followed by drying and post-treatment to obtain the cleaned semiconductor alloy parts.

[0047] Preparation steps of phytate-glucosyl silane alloy compound:

[0048] A1. Add 65.0g deionized water, 8.0g sodium gluconate, 0.5g sodium citrate, and 1.0g polyethylene glycol 400 to a reaction vessel. Stir at 35℃ for 20min to completely disperse and dissolve the sodium gluconate, sodium citrate, and polyethylene glycol 400. Add 6.0g phytic acid aqueous solution, add ammonia dropwise and adjust the pH to 6.8. Continue stirring until the system is clear or uniformly dispersed to obtain a phytic acid-sodium gluconate pre-complexed solution. Separately, add 8.0g anhydrous ethanol, 1.5g 3-aminopropyltriethoxysilane, 2.0g deionized water, and 0.10g glacial acetic acid to another reaction vessel. Stir and hydrolyze at 20℃ for 30min to obtain a silane pre-hydrolyzed solution. Slowly add the silane pre-hydrolyzed solution to the phytic acid-sodium gluconate pre-complexed solution while stirring. Add ammonia dropwise and adjust the pH to 7.0. Stir at 40℃ for 1.0h to obtain a phytic acid-sodium gluconate-silane composite solution.

[0049] A2. The phytate-glucosyl silane composite solution was aged at 40℃ for 1.0h, cooled to 25℃, and 0.05g of 1,2-benzisothiazolin-3-one was added. The mixture was stirred until homogeneous, allowed to stand for 1h to defoam, and then filtered to obtain the phytate-glucosyl silane alloy compound.

[0050] Preparation steps of carboxybetaine polyether desiliconized compound:

[0051] B1. Add 55.0g deionized water, 3.0g polyethylene glycol 400, 2.0g sodium citrate, and 0.3g tetrasodium hydroxyethylidene diphosphonate to a reaction vessel and stir at 35°C for 20 minutes to fully dissolve and disperse the polyethylene glycol 400, sodium citrate, and tetrasodium hydroxyethylidene diphosphonate, obtaining a polyether dispersion base solution. Add 8.0g cocamidopropyl betaine aqueous solution, 3.0g fatty alcohol polyoxyethylene ether, and 4.0g isopropanol to the polyether dispersion base solution and continue stirring until the system is homogeneous to obtain a betaine polyether compound solution.

[0052] B2. Add 2.0g of low molecular weight sodium polyacrylate aqueous solution to the betaine polyether compound solution, adjust the pH to 7.8 by dropwise addition, mature at 40℃ for 1h, cool to 25℃, add 0.03g of polyether modified polydimethylsiloxane defoamer, continue stirring until the system is uniform, let stand for defoaming for 1h, filter, and obtain carboxybetaine polyether desiliconized compound.

[0053] Example 3

[0054] The difference between this embodiment and Embodiment 1 is that this embodiment provides a cleaning process for semiconductor alloy components, including the following steps:

[0055] S1. Add 150.0g deionized water, 2.4g sodium carbonate, 1.2g sodium bicarbonate and 0.45g sodium citrate to the cleaning solution preparation container and stir until completely dissolved to obtain a weakly alkaline base solution; add 0.25g sodium dodecyl sulfate, 0.30g fatty alcohol polyoxyethylene ether, 6.0g isopropanol, 0.80g sodium phytate silane alloy compound and 1.20g carboxybetaine polyether desiliconizing compound to the weakly alkaline base solution, continue mixing for 40min, adjust the pH to 9.2, filter, and obtain a weakly alkaline composite cleaning solution;

[0056] S2. The surface of the machined semiconductor alloy parts is pretreated to remove burrs, rough spots and loose particles to obtain pre-polished parts; dry compressed air at a pressure of 0.6 MPa is used to blow along the machining texture of the pre-polished parts in the opposite direction for 8 minutes to obtain blown parts; the threaded holes, blind holes, grooves, flow channels, mating surfaces and sealing surfaces of the blown parts are cleaned with 120.0 g of high-pressure deionized water for 30 seconds to obtain pre-de-powdered parts;

[0057] S3. The pre-de-powdered parts are ultrasonically coarsely cleaned for 15 minutes at 60°C with 150.0g of weak alkaline composite cleaning solution to obtain coarsely cleaned parts; the coarsely cleaned parts are ultrasonically rinsed with 120.0g of deionized water for 8 minutes, and then ultrasonically finely rinsed with 120.0g of deionized water for 5 minutes to obtain rinsed parts; the rinsed parts are then scanned line by line with 120.0g of high-pressure deionized water for 30 seconds to obtain replenished parts; 90.0g of isopropanol and 10.0g of deionized water are mixed to obtain an isopropanol aqueous solution, and the replenished parts are ultrasonically cleaned with the isopropanol aqueous solution, and then sprayed, immersed, and overflowed with 120.0g of deionized water in sequence, followed by drying and post-treatment to obtain the cleaned semiconductor alloy parts.

[0058] Preparation steps of phytate-glucosyl silane alloy compound:

[0059] A1. Add 85.0g deionized water, 14.0g sodium gluconate, 2.0g sodium citrate, and 4.0g polyethylene glycol 400 to a reaction vessel. Stir at 45℃ for 30 minutes to completely disperse and dissolve the sodium gluconate, sodium citrate, and polyethylene glycol 400. Add 12.0g phytic acid aqueous solution, and add ammonia dropwise to adjust the pH to 7.6. Continue stirring until the system is clear or uniformly dispersed to obtain a phytic acid-sodium gluconate pre-complexed solution. 14.0 g anhydrous ethanol, 3.5 g 3-aminopropyltriethoxysilane, 6.0 g deionized water and 0.40 g glacial acetic acid were added to another reaction vessel and hydrolyzed at 30 °C for 60 min to obtain a silane pre-hydrolyzed solution. The silane pre-hydrolyzed solution was slowly added to the sodium phytate pre-complexed solution while stirring. Ammonia was added dropwise and the pH was adjusted to 7.4. The mixture was stirred at 50 °C for 2.5 h to obtain a sodium phytate silane composite solution.

[0060] A2. The phytate-glucosyl silane composite solution was aged at 55℃ for 2.0h, cooled to 35℃, and 0.15g of 1,2-benzisothiazolin-3-one was added. The mixture was stirred until homogeneous, allowed to stand for 3h to defoam, and then filtered to obtain the phytate-glucosyl silane alloy compound.

[0061] Preparation steps of carboxybetaine polyether desiliconized compound:

[0062] B1. Add 75.0g deionized water, 8.0g polyethylene glycol 400, 5.0g sodium citrate, and 1.2g tetrasodium hydroxyethylidene diphosphonate to a reaction vessel and stir at 45℃ for 40min to fully dissolve and disperse the polyethylene glycol 400, sodium citrate, and tetrasodium hydroxyethylidene diphosphonate to obtain a polyether dispersion base solution. Add 15.0g cocamidopropyl betaine aqueous solution, 7.0g fatty alcohol polyoxyethylene ether, and 8.0g isopropanol to the polyether dispersion base solution and continue stirring until the system is homogeneous to obtain a betaine polyether compound solution.

[0063] B2. Add 5.0g of low molecular weight sodium polyacrylate aqueous solution to the betaine polyether compound solution, adjust the pH to 8.6 by dropwise addition, mature at 50℃ for 2h, cool to 35℃, add 0.12g of polyether modified polydimethylsiloxane defoamer, continue stirring until the system is uniform, let stand for defoaming for 3h, filter, and obtain carboxybetaine polyether desiliconized compound.

[0064] Comparative Example 1

[0065] The difference between this comparative example and Example 1 is that 0.525g of sodium phytate silane alloy compound is not added in S1, and 0.525g of deionized water is used instead; otherwise, it is the same as Example 1.

[0066] Comparative Example 2

[0067] The difference between this comparative example and Example 1 is that 0.775g of carboxybetaine polyether desiliconizing compound is not added in S1, and 0.775g of deionized water is used instead. The rest is the same as in Example 1.

[0068] Comparative Example 3

[0069] The difference between this comparative example and Example 1 is that 0.525g of sodium phytate silane alloying compound and 0.775g of carboxybetaine polyether desiliconizing compound are not added in S1, and 1.300g of deionized water is used instead. The rest is the same as in Example 1.

[0070] A series of standardized tests were conducted on the cleaning processes of the semiconductor alloy components described in Examples 1-3 and Comparative Examples 1-3, respectively.

[0071] Semiconductor alloy parts of the same batch, material, machining process and structural size were selected as test samples. They were treated according to the cleaning processes of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively. Each group was set with n=5. After cleaning, the samples were placed in a clean environment of 23℃ and 50%RH for 2 hours to equilibrate before testing.

[0072] Surface particle residue testing: Each sample was tested using a KLA-Tencor Surfscan SP series surface particle detection device (or an equivalent laser scattering surface particle scanner with a particle size detection limit ≤ 0.3 μm). The detection area and effective area were calculated as follows: For continuous planar areas such as mating surfaces and sealing surfaces, they were treated as a continuous detection area for full-area scanning, with a single-area effective scanning area ≥ 5 cm². 2 The actual projected area of ​​the scanned region is used as the effective detection area. For discontinuous planar structures such as threaded openings, blind openings, groove edges, and flow channel outlets, a high-resolution optical microscope (200× magnification) is used in conjunction with image recognition software (such as ImageJ) for statistical analysis. The projection plane of the opening (or the opening plane contour of the groove / flow channel outlet) is used as the effective detection area. Five openings are selected for each structural location for detection. The effective area of ​​a single opening is determined after calibration on the sample CAD drawing, and the developed area of ​​the hole wall is not used. Ten detection points are selected for each sample. The lower limit of particle size statistics is 0.3μm. The number of particles in the three ranges of 0.3-1μm, 1-5μm, and ≥5μm are recorded respectively. After removing abnormal contamination points (detection points where the number of particles in a single point exceeds three times the standard deviation of the mean of the whole group), the average value of all detection points in each group is calculated. The result is the total number of particles with a particle size ≥0.3μm, and the unit is particles / cm. 2 .

[0073] In subsequent powder shedding tests, the cleaned and dried sample was fixed on a clean testing platform with the mating surfaces, threaded holes, blind holes, grooves, and flow channel outlets facing the clean collection plate. These areas were continuously purged with 0.3 MPa dry compressed air for 60 seconds at a distance of 50 mm. After purging, the collection plate was left to stand in a clean environment for 5 minutes. A surface particle detection device was used to count the number of particles ≥5 μm on the collection plate, and the result was calculated based on the effective test area of ​​the sample. The unit of the result is particles / cm². 2 .

[0074] For the white wiping color difference test, take a pre-cleaned lint-free cloth and soak it in anhydrous ethanol, keeping the cloth moist but without dripping. Under 10N pressure, wipe the sample mating surface, sealing surface, and groove edge 10 times in the same direction. The wiping area is 10cm². 2 After wiping, the cleanroom cloth was placed in an environment of 23℃ and 50%RH for 10 minutes to evaporate naturally. The color difference value of the cleanroom cloth before and after wiping was measured using a colorimeter. Three positions were tested for each sample, and the average value was taken as the white wiping color difference value.

[0075] During the surface roughness increase test, five fixed detection positions were marked on the mating surface and sealing surface of each sample before cleaning. The Ra value of each detection position was measured using a surface roughness meter. After cleaning and drying, the Ra value was measured again at the same position. The Ra value after cleaning minus the Ra value before cleaning was taken as the single-point surface roughness increase. The average value of 10 detection positions was taken for each sample, and the average value of n=5 was taken for each group. The unit of the result is μm.

[0076] For the mass loss test, the sample to be cleaned was dried at 80℃ for 30 minutes, then cooled to 23℃ and weighed initially. After cleaning, it was dried and cooled under the same conditions and weighed finally. The mass difference was obtained by subtracting the initial mass from the final mass, and then divided by the effective immersion area of ​​the sample to obtain the mass loss per unit area. The result is expressed in mg / cm². 2 .

[0077] For the cleaning agent residue test, the cleaned and dried sample was placed in a clean container. The sample surface, threaded holes, blind holes, grooves, and flow channels were quantitatively rinsed with 50 mL of deionized water for 120 s. After collecting all the rinsing solution, the total organic carbon content was determined and converted to the residue per unit area based on the effective test area of ​​the sample. The result is expressed in μg / cm². 2 .

[0078] The performance test data above are shown in Table 1.

[0079] Table 1 Performance Test Results

[0080] Test Project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Surface particle residual count (pieces / cm 2 )]]> 8.6 10.4 7.9 14.8 32.6 45.3 <![CDATA[Subsequent powder shedding amount (pieces / cm 2 )]]> 3.1 4.2 2.8 6.5 18.7 27.4 White wiping color difference value 1.2 1.5 1.1 1.8 4.6 6.2 Increase in surface roughness (μm) 0.018 0.026 0.021 0.084 0.031 0.096 <![CDATA[Mass loss (mg / cm 2 )]]> 0.042 0.058 0.049 0.186 0.064 0.214 <![CDATA[Cleaning agent residual amount (μg / cm 2 )]]> 0.38 0.43 0.41 0.45 0.62 0.78

[0081] As can be seen from the above, Examples 1-3 effectively solve the technical problems of incomplete removal of silicon powder and fine particles, subsequent powder shedding from complex hole and groove structures, secondary adhesion of particles, roughening and corrosion of alloy surface caused by weak alkaline cleaning, and insufficient control of residues after cleaning in the existing semiconductor alloy component cleaning process compared with Comparative Examples 1-3.

[0082] The surface particle residue in Examples 1-3 was 8.6 particles / cm³. 2 10.4 pieces / cm 2 and 7.9 per cm 2 This is significantly lower than the 32.6 cells / cm² in Comparative Example 2. 2 Compared to 45.3 per cm in Comparative Example 3 2 This indicates that adding carboxybetaine polyether desiliconizing compound to the weak alkaline composite cleaning solution can enhance the cleaning solution's ability to wet, peel off, and suspend and disperse silicon powder in processed textures, threaded holes, blind holes, grooves, and flow channels, thereby reducing particle re-adhesion and secondary deposition during the cleaning process.

[0083] The subsequent powder loss in Examples 1-3 was 3.1 particles / cm², respectively. 2 4.2 pieces / cm 2 and 2.8 per cm 2 It was also significantly lower than the 18.7 cells / cm² of control example 2. 2 Compared to 27.4 per cm in Comparative Example 3 2 This indicates that the process described in the embodiment can not only remove surface powder, but also reduce the risk of release of residual particles inside the holes and processing textures during subsequent purging or use.

[0084] The white wiping color difference values ​​of Examples 1-3 were 1.2, 1.5 and 1.1, respectively, which were significantly lower than 4.6 of Comparative Example 2 and 6.2 of Comparative Example 3, indicating that there were fewer gray silicon powder traces and higher surface cleanliness after cleaning in the Examples.

[0085] Comparative Example 1, without the addition of sodium phytate-glucan silane alloying compound, showed lower surface particle residue and subsequent powder loss compared to Comparative Examples 2 and 3. However, its surface roughness increased by 0.084 μm, and its mass loss reached 0.186 mg / cm². 2 The concentrations were significantly higher than those in Examples 1-3 (0.018-0.026 μm and 0.042-0.058 mg / cm³). 2 This indicates that when phytic acid-glucosyl silane is lacking in the alloying compound, the weak alkaline cleaning system provides insufficient protection for the alloy matrix, which can easily lead to surface roughening and material loss.

[0086] Comparative Example 2, which did not contain carboxybetaine polyether desiliconizing compound, showed relatively low increases in surface roughness and mass loss, but significantly increased levels of residual particles, subsequent powder loss, and white wiping color difference. This indicates that relying solely on the protective alloy component cannot adequately solve the problems of silicon powder stripping and particle redeposition.

[0087] Comparative Example 3, lacking both sodium phytate-glucosyl silane alloying compound and carboxybetaine polyether desiliconizing compound, exhibited the following effects: residual surface particles, subsequent powder shedding, white wiping color difference, increase in surface roughness, mass loss, and residual cleaning agent, all reaching 45.3 particles / cm². 2 27.4 per cm 2 ,6.2,0.096μm,0.214mg / cm 2 and 0.78 μg / cm 2 The results were all at a poor level, further demonstrating that the phytate-glucosyl silane alloying compound and the carboxybetaine polyether desiliconizing compound have a synergistic effect in alloy corrosion inhibition, wetting and desiliconization, particle dispersion and residue reduction.

[0088] Therefore, it can be seen that the combination of weak alkaline composite cleaning solution, pre-de-powdering, high-pressure deionized water replenishment, ultrasonic rough cleaning, ultrasonic rinsing, ultrasonic fine rinsing, line-by-line scanning replenishment, isopropanol aqueous solution ultrasonic cleaning and multi-stage deionized water rinsing in Examples 1-3 can significantly reduce particle residue, subsequent powder shedding and cleaning agent residue while maintaining the stability of the alloy surface, thereby improving the thoroughness of cleaning and the stability of use of semiconductor alloy components.

Claims

1. A cleaning process for alloy components used in semiconductors, characterized in that the steps include... include: S1. Mix deionized water, sodium carbonate, sodium bicarbonate and sodium citrate to obtain a weakly basic solution; Add sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, isopropanol, sodium phytate silane alloying compound, and carboxy betaine polyether desiliconizing compound to a weak alkaline base solution, continue mixing, adjust the pH, filter, and obtain a weak alkaline composite cleaning solution. S2. The surface of the semiconductor alloy parts is pretreated, blown with compressed air, and washed with high-pressure deionized water in sequence to obtain pre-de-powdered parts. S3. The pre-de-powdered parts are ultrasonically coarsely cleaned with a weak alkaline composite cleaning solution to obtain coarsely cleaned parts; then the coarsely cleaned parts are cleaned, dried and post-treated.

2. The cleaning process for semiconductor alloy components according to claim 1, characterized in that, In step S1, the amounts of deionized water, sodium carbonate, sodium bicarbonate, sodium citrate, sodium dodecyl sulfate, fatty alcohol polyoxyethylene ether, isopropanol, sodium phytate silane alloying compound, and carboxybetaine polyether desiliconizing compound, by weight, are respectively: 100.0-150.0 parts, 1.0-2.4 parts, 0.4-1.2 parts, 0.10-0.45 parts, 0.05-0.25 parts, 0.05-0.30 parts, 2.0-6.0 parts, 0.25-0.80 parts, and 0.35-1.20 parts; the fatty alcohol polyoxyethylene ether is fatty alcohol polyoxyethylene ether AEO-9; the pH is adjusted to 8.2-9.

2.

3. The cleaning process for semiconductor alloy components according to claim 1, characterized in that, In step S2, the pressure of the compressed air is 0.4-0.6 MPa.

4. The cleaning process for semiconductor alloy components according to claim 1, characterized in that, In step S3, the amount of the weak alkaline composite cleaning solution used is 80.0-150.0 parts by weight.

5. The cleaning process for semiconductor alloy components according to claim 1, characterized in that, The preparation method of the phytate-glucosyl silane alloy compound includes: A1. By weight, mix 65.0-85.0 parts deionized water, 8.0-14.0 parts sodium gluconate, 0.5-2.0 parts sodium citrate, and 1.0-4.0 parts polyethylene glycol 400, and stir at 35-45℃. Add 6.0-12.0 parts phytic acid aqueous solution, adjust the pH to 6.8-7.6 with ammonia water, and continue stirring to obtain a phytic acid-sodium gluconate pre-complexed solution; add 8.0-1... 4.0 parts anhydrous ethanol, 1.5-3.5 parts 3-aminopropyltriethoxysilane, 2.0-6.0 parts deionized water and 0.10-0.40 parts glacial acetic acid are mixed and hydrolyzed at 20-30℃ to obtain a silane pre-hydrolyzed solution; the silane pre-hydrolyzed solution is added to a sodium phytate pre-complexing solution, the pH is adjusted to 7.0-7.4 with ammonia water, and the mixture is stirred at 40-50℃ to obtain a sodium phytate silane composite solution; A2. The phytate-glucosyl silane composite solution is aged at 40-55℃, cooled to 25-35℃, 0.05-0.15 parts of 1,2-benzisothiazolin-3-one are added, stirred, allowed to stand to defoam, and filtered.

6. The cleaning process for semiconductor alloy components according to claim 5, characterized in that, In step A1, the stirring time at 20-30℃ is 30-60 min; the stirring time at 40-55℃ is 1.0-2.5 h.

7. The cleaning process for semiconductor alloy components according to claim 5, characterized in that, In step A2, the maturation time at 40-55℃ is 1.0-2.0h, and the standing time for defoaming is 1-3h.

8. The cleaning process for semiconductor alloy components according to claim 1, characterized in that, The preparation method of the carboxybetaine polyether desiliconized compound includes: B1. By weight, mix 55.0-75.0 parts deionized water, 3.0-8.0 parts polyethylene glycol 400, 2.0-5.0 parts sodium citrate and 0.3-1.2 parts tetrasodium hydroxyethylidene diphosphonate, and stir at 35-45℃ to obtain a polyether dispersion base solution; add 8.0-15.0 parts cocamidopropyl betaine aqueous solution, 3.0-7.0 parts fatty alcohol polyoxyethylene ether and 4.0-8.0 parts isopropanol to the polyether dispersion base solution, and stir to obtain a betaine polyether compound solution; B2. Add 2.0-5.0 parts of low molecular weight sodium polyacrylate aqueous solution to the betaine polyether compound solution, adjust the pH to 7.8-8.6, mature at 40-50℃, cool to 25-35℃, add 0.03-0.12 parts of polyether modified polydimethylsiloxane defoamer, stir, let stand to defoam, and filter.

9. The cleaning process for semiconductor alloy components according to claim 8, characterized in that, In step B1, the stirring time at 35-45℃ is 20-40 minutes.

10. The cleaning process for semiconductor alloy components according to claim 8, characterized in that, In step B2, the maturation time at 40-50℃ is 1-2 hours; the standing defoaming time is 1-3 hours.